Mathematics - Pelangi Multimedia Technologies Sdn. Bhd.; Penerbitan Pelangi Sdn. Bhd. (Selangor : Pelangi Multimedia Technologies Sdn. Bhd. : Penerbitan Pelangi Sdn. Bhd. (marketer), 2006)
This program consists of 6 main sections, namely tutorial, interactive zone, e-test, summary, memory enhancer and answering strategy in mathematics from form 1 to form 3. Besides, there are few tools that is of great help when using the program, which is bookmark, index, glossary, print, configuration and help
jilid 1. Mathematics form 1 - jilid 2. Mathematics form 2 - jilid 3. Mathematics form 3
System Requirements : Windows 98/ME/2000/XP, processor speed of 800MHz above, multimedia PC spekaer, mouse and keyboard, 256 MB RAM and above
Keywords: Mathematics -- Study and teaching (Secondary); Mathematics -- Problems, exercises, etc